Low-noise, low-power transimpedance amplifier for integrated electrochemical biosensor applications - Wilson, William, author; Chen, Tom, advisor; Pezeshki, Ali, committee member; Henry, Chuck, committee member (Colorado State University. Libraries, 2014)
Biosensor devices have found an increasingly broad range of applications including clinical, biological, and even pharmaceutical research and testing. These devices are useful for detecting chemical compounds in solutions and tissues. Current visual or optical methods include fluorescence and bio/chemiluminescence based detection. These methods involve adding luminescent dyes or fluorescent tags to cells or tissue samples to track movement in response to a stimulus. These methods often harm living tissue and interfere with natural cell movement and function. Electrochemical biosensing methods may be used without adding potentially harmful dyes or chemicals to living tissues. Electrochemical sensing may be used, on the condition that the desired analyte is electrochemically active, and with the assumption that other compounds present are not electrochemically active at the reduction or oxidation potential of the desired analyte. A wide range of analytes can be selectively detected by specifically setting the potential of the solution using a potentiostat. The resulting small-magnitude current must then be converted to a measurable voltage and read using a low-noise transimpedance amplifier. To provide spatial resolution on the intra-cellular level, a large number of electrodes must be used. To measure electrochemical signals in parallel, each electrode requires a minimum of a transimpedance amplifier, as well as other supporting circuitry. Low power consumption is a requirement for the circuitry to avoid generating large amounts of heat, and small size is necessary to limit silicon area. This thesis proposes the design of a low-noise, low-power transimpedance amplifier for application in integrated electrochemical biosensor devices. The final proposed design achieves a 5MΩ transimpedance gain with 981aA/√Hz input inferred noise, 8.06µW at 0.9V power supply, and occupies a silicon area of 0.0074mm2 in a commercial 0.18µm CMOS process. This thesis also explores the development of a multi-channel electrochemical measurement system.
Keywords: biosensor; transimpedance; low-power; integrated; electrochemistry